The Relevance of the Concept of Hadith Jawami’ al-Kalim in the Information Era: New Strategies for Spreading the Wisdom of Islam - Zakiar, Zakiar (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study examines the relevance of the Jawami’ al-Kalim hadith concept in spreading Islamic wisdom in the information age. Jawami’ al-Kalim refers to the principle of conveying Islamic teachings concisely yet comprehensively. Using literature review and content analysis methods, this research evaluates digital da'wah strategies that apply the Jawami’ al-Kalim principle. Primary and secondary sources are analyzed to identify best practices in spreading Islamic messages through digital media. The results show the effectiveness of utilizing social media, developing online educational content, and collaborating with Muslim influencers. These strategies allow Islamic da'wah to reach a wider audience, build solid online communities, and respond to contemporary issues. Although facing challenges such as misinformation, this approach opens new opportunities to strengthen religious education and positive inspiration in global society. In conclusion, applying the Jawami’ al-Kalim principle through digital technology is an important step in ensuring the relevance and effectiveness of Islamic da'wah in the information age.